Affective Consciousness in La Nausée - Benjamin Suhl (Studies in 20th & 21st Century Literature, 1978)
La Nausée, a key to Sartre's work, centers on an affective comprehension of the world, which becomes cognitive in the author's philosophy. Nausea is the affective equivalent of Descartes's systematic doubt and of Husserl's reduction. The recent publication of Sartre's earliest writings permits us to isolate his fundamental concerns, later to be developed in the novel: contingency and its evasion in bad faith. A certain Antoine Roquentin is shaken by the fear of becoming submerged in Bouville, physically and socially. He passes through an acute crisis, recorded blow by blow in his diary. It leads to a radical change of his fundamental project. Roquentin comes to realize that he cannot attain being as a historian. Nor can he make of his life an art, as his friend Anny had tried to do so unsuccessfully. The imaginary, however, can be a vehicle to a heightened awareness of reality. Thus a rag-time tune, authentic in its expression of forlornness, becomes a leitmotif of commitment. Roquentin's failure to intervene forcefully to save Lucienne and to protect the Autodidacte weighs on him. He determines to seek in literary commitment an antidote for himself and for others against the all-pervasive spirit of seriousness of the dominant ideology.
Keywords: La Nausée; Jean Paul Sartre; philosophy; contingency; Nausea